PENGARUH EKSPERIMEN PAPIER MACHE TERHADAP KREATIVITAS ANAK USIA 5-6 TAHUN DI PAUD ANANDA TAHUN AJARAN 2025/2026 - Ronita Lena Sari Silaban; Endang Junita Sinaga; Uranus Zamili (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study was to determine the effect of papier-mâché experiments on the creativity of children aged 5–6 years at PAUD Ananda. This study employed a pre-experimental research method using a One Group Pretest–Posttest Design. The population consisted of all children aged 5–6 years at PAUD Ananda, totaling 25 students, and the entire population was used as the research sample. Data were collected using an observation sheet consisting of 15 items to assess children’s creativity.The results of the data analysis showed that papier-mâché experiments had a significant effect on the creativity of children aged 5–6 years at PAUD Ananda. This was indicated by the increase in the average posttest score, which was 54.88, compared to the average pretest score of 29.88. The difference between the pretest and posttest mean scores was 25.32, indicating a clear improvement in children’s creativity after the implementation of the papier-mâché experiment. In addition, the significance test showed that the calculated t-value was greater than the table t-value at a significance level of 0.05 with 24 degrees of freedom (6.332 > 2.060). Therefore, the null hypothesis (H₀) was rejected, and the alternative hypothesis (Hₐ), stating that papier-mâché experiments significantly affect the creativity of children aged 5–6 years at PAUD Ananda, was accepted.